Chloroplast Genome Sequencing and Comparative Analysis of Six Medicinal Plants of Polygonatum - Jinchen Yao; Zhaohuan Zheng; Tao Xu; Duomei Wang; Jingzhe Pu; Yazhong Zhang; Liangping Zha (Ecology and Evolution, 2025)
ABSTRACT The genus Polygonatum boasts abundant germplasm resources and comprises numerous species. Among these, medicinal plants of this genus, which have a long history, have garnered attention of scholars. This study sequenced and analyzed the chloroplast genomes of six species of Polygonatum medicinal plants (P. zanlanscianense, P. kingianum, P. sibiricum, P. cyrtonema, P. filipes, and P. odoratum, respectively) to explore their interspecific relationships. The sequence length (154, 578–155, 807 bp) and genome structure were conserved among the six Polygonatum species, with a typical tetrad structure. Among the 127–131 genes contained in the genomes, 84–85 are protein‐coding genes, 37–38 are transfer RNA genes, and 6–8 are ribosomal RNA genes. The genomes contained 64–76 simple sequence repeats (SSRs) and 36–62 long repetitive sequences. Codon bias patterns tended to use codons ending in A/T. In 30 types of codons with RSCU > 1, 93.3% ended in A/T of the six species. Twenty‐one highly variable plastid regions were identified in the chloroplast genomes of the six medicinal plants. Furthermore, a phylogenetic analysis encompassing these and 53 other chloroplast genomes of Polygonatum species revealed that P. cyrtonema, P. odoratum, and P. filipes clustered together on one clade, whereas P. kingianum and P. zanlanscianense formed separate clades. Notably, P. sibiricum emerged as a standalone clade, and our phylogenetic tree reinforces the classification of P. sibiricum as forming a monophyly. This study provides a novel basis for intragenus taxonomy and DNA barcoding molecular identification within the genus Polygonatum medicinal plants.